Effects of slough clearance rates post adult tonsillectomy in patients with laryngopharyngeal reflux disease - L., Manoj Kumar; Shree N., Raadhika; K. H., Anand (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Laryngopharyngeal reflux is known to be associated with multiple disease of the upper aero digestive tract and can cause serious injury to the mucosa long term. Methods: Patients diagnosed with chronic tonsillitis and indicated for surgery were evaluated for laryngopharyngeal reflux using reflux symptom index score. When score greater than 13 was suggestive of laryngopharyngeal reflux (LPR) and counselled for 24 hours ambulatory dual probe pH monitoring. When the reflux event was 7 or more were diagnosed having LPR. Patients were divided into two groups Group A patients with chronic tonsillitis and without LPR and Group B patients with chronic tonsillitis and LPR. Postoperatively there slough percentage was calculated as 25%, 50%, 75%, 100% on the postoperative day (POD) 7, 14 and 21. Slough clearance rates were calculated as 100- slough percentage. Results: There were 40 patients in Group A and 40 patients in Group B. The slough clearance rates of Group A were 46.3, 73.8 and 96.9 on post-operative days 7, 14, 21 respectively. The slough clearance rates of Group B were 30.1, 57.6, 90.1 on POD 7, 14, 21 respectively. The p values comparing slough clearance rates showed 0.00, 0.002, 0.013 on POD 7, 14, 21 which was statistically significant. Group B with laryngopharyngeal reflux had delayed healing than Group A. Conclusions: Laryngopharyngeal reflux seems to adversely affect healing and complication following tonsillectomy due to lowering of slough clearance rates. Hence we recommend the need for assessment and treatment pre/post operatively of laryngopharyngeal reflux disease in adult patients undergoing tonsillectomy.